Reaction of short-season soybean variety to pre-sowing UV treatment of seeds - Mikhailova M.P.; Gretchenko A.E.; Blinova A.A. (BIO Web of Conferences)
This paper presents the results of studies on the effect of ultraviolet treatment on seed quality, initial growth, enzymatic activity and productivity of soybean plants. The object of studies were the seeds and plants of the Alpetra short-season soybean variety, bred by the All-Russian Scientific Research Institute of Soybean. Seeds were treated at the Joint Institute for High Temperatures of the Russian Academy of Sciences in 2024. Field studies were carried out on the experimental field of FSBSI FSC All-Russian Scientific Research Institute of Soybean, located in the southern agroclimatic zone of the Amur region (Sadovoye village, Tambovka district). The experimental scheme included the following treatments: 1. Check (no treatment); 2. UV (exposure – 1 minute); 3. UV (exposure – 3 minutes); 4. UV (exposure – 5 minutes). Laboratory experiments were conducted in the laboratory of plant physiology and biochemistry. The activity of ascorbate oxidase and guaiacol peroxidase was determined by spectrophotometric method, protein content – by Lowry method. Studies showed that the pre-sowing treatment of soybean seeds had a positive influence on the initial stages of germination. Germination energy and laboratory germination capacity increased by 6 and 3% respectively relative to the check variant. The highest average length of 10-day soybean germs treated with UV radiation was observed when exposed to UV for 5 minutes. The value of the check variant was exceeded by 4.2 cm. A change in the total protein content was also noted. In the variant when seeds were treated with ultraviolet for 5 minutes, the content of protein increased by 0.53% as compared with the check variant. UV-treatment of soybean seeds of the Alpetra variety with a 5-minute exposure increased biological yield by 0.20 t/ha (НСР05 = 0.18 t/ha).